2013
DOI: 10.1021/jm400959q
|View full text |Cite
|
Sign up to set email alerts
|

An Epoxyisoprostane Is a Major Regulator of Endothelial Cell Function

Abstract: The goal of these studies was to determine the effect of 5,6-epoxyisoprostane, EI, on human aortic endothelial cells (HAEC). EI can form as a phospholipase product of 1-palmitoyl-2-(5,6-epoxyisoprostane E2)-sn-glycero-3-phosphocholine, PEIPC, a pro-inflammatory molecule that accumulates in sites of inflammation where phospholipases are also increased. To determine the effect of EI on HAEC, we synthesized several stereoisomers of EI using a convergent approach from the individual optically pure building blocks,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 32 publications
(81 reference statements)
0
22
0
Order By: Relevance
“…Transcriptional changes of multiple genes in dose-response experiments, using varying concentrations of OxPAPC and HDL, are inconsistent with nonspecifi c sequestration of OxPAPC by HDL. This is further supported by the fact by guest, on May 11, 2018 www.jlr.org effects of EI, which regulates many of the same genes as OxPAPC and PEIPC ( 28 ), are undiminished by cotreatment with HDL. Additional research may identify other bioactive constituents of OxPAPC, or products of OxPAPC degradation, which remain active toward HAECs in the presence of HDL.…”
Section: Hdl Effects On Transcription In the Presence And Absence Of mentioning
confidence: 81%
See 2 more Smart Citations
“…Transcriptional changes of multiple genes in dose-response experiments, using varying concentrations of OxPAPC and HDL, are inconsistent with nonspecifi c sequestration of OxPAPC by HDL. This is further supported by the fact by guest, on May 11, 2018 www.jlr.org effects of EI, which regulates many of the same genes as OxPAPC and PEIPC ( 28 ), are undiminished by cotreatment with HDL. Additional research may identify other bioactive constituents of OxPAPC, or products of OxPAPC degradation, which remain active toward HAECs in the presence of HDL.…”
Section: Hdl Effects On Transcription In the Presence And Absence Of mentioning
confidence: 81%
“…The 5,6-epoxyisoprostane (EI) was synthesized as described previously, and a single analog, EI4, was used in this study ( 28 ). Cholesterol-cyclodextrin complex was purchased from Sigma-Aldrich.…”
Section: Reagentsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we showed that fatty acid fraction of OxPAPC, specifically epoxyisoprostane E2, possess the same activity of OxPAPC/PEIPC in stimulating superoxide production and the expression of OKL38 and HO-1 in endothelial cells. We most recently showed that EI also modulated the expression of other genes regulated by OxPAPC[12]. The net effect of EI on atherosclerosis will be the interest of future study.…”
Section: Discussionmentioning
confidence: 99%
“…We have previous shown that the sn-2 position is required for the activity of OxPAPC in stimulating monocyte binding and gene expression in endothelial cells[9,10]. Our most recent studies demonstrate that EI, the PLA2 hydrolysis product of PEIPC, though poorly regulating inflammatory function, is able to regulate 40% of the genes regulated by PEIPC[12]. This study examines the ability of EI to regulate oxidative stress.…”
Section: Introductionmentioning
confidence: 99%